Mood states and quality of life in Paralympic Boccia athletes in the Covid-19 pandemic - De Arruda, S. F.; De Oliveira, J. I. V.; Dantas, M. J. B.; Da Cunha Costa, M.; Guedes Leite de Oliveira, L. I.; Melo de Oliveira, S. F. (Revista Brasileira de Medicina do Esporte, 2022)
Introduction: Although studies have been conducted in the athlete population during the pandemic, its impacts on Paralympic athletes are still unknown.